VECD investigation and quantification of rest period healing within pulse-rest loading - Su, Y.; Asadi, H.; Nikraz, Hamid (Taylor & Francis, 2019)
The viscoelastic continuum damage (VECD) model has been widely recognised as a characterisation method for asphalt mixture’s fatigue and damage behaviour. Rest periods between loading cycles can recover stiffness and extend fatigue life. However, there is still a lack of approach to quantify the effect of rest period after each load cycle (pulse-rest loading). In this paper, a series of simplified VECD tests are conducted with different length of rest period. Based on smeared continuum damage method, rest period based damage characteristic curves are produced at two different temperatures, with rest period healing effect critically evaluated. VECD results indicate that longer rest period improves healing effect, and higher temperature incurs greater maximum healing effect when rest period is long. Based on regression fitting technique, a novel rest period damage function has been developed. The new function can be used to overcome laboratory fluctuation of VECD tests with pulse-rest loading, to produce accurate smeared damage characteristic curves with any rest period length. It has benefit of saving experiment time and improving accuracy. This work also proposes laboratory procedures and data processing notices for the production of rest period damage functions for future use.